48y-4(6-y)=12(3y+2)

Simple and best practice solution for 48y-4(6-y)=12(3y+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 48y-4(6-y)=12(3y+2) equation:


48y-4(6-y)=12(3y+2)

We simplify the equation to the form, which is simple to understand
48y-4(6-y)=12(3y+2)

Reorder the terms in parentheses
48y+(-24+4y)=12*(3y+2)

Remove unnecessary parentheses
+48y-24+4y=+12+*(+3y+2+)

Reorder the terms in parentheses
48y-24+4y=+(+36y+24)

Remove unnecessary parentheses
+48y-24+4y=+36y+24

We move all terms containing y to the left and all other terms to the right.
+48y+4y-36y=+24+24

We simplify left and right side of the equation.
+16y=+48

We divide both sides of the equation by 16 to get y.
y=3

See similar equations:

| -3x-14=1 | | fu=3 | | -7(x+8)=35 | | 175x^2-28=0 | | 3a+9b-12= | | 4x+19=7-2x | | -5+4a+3a+6=0 | | 2x-8y=-34 | | -3(x-4)+10=-2 | | -49+9=-5 | | (7x+2)(3x-y)= | | 6(x+4)=3(4-2) | | x(7)=49 | | 2x^2=5-5x | | 3(2x-1)+9=2(3x+3) | | y=28(3)+10 | | 3.2-1.8x=-1.3 | | X^2+10=-25 | | -2x-7(-8x-16)=4 | | y=28x+10 | | 3.14*30*30*-=9420 | | 6-5x=-2 | | 3(5v+4)-(1-v)=-1+5v+1 | | -2x-7(8x-16)=4 | | 15=8-5(c+7) | | 18+y-1=16+y | | 4g=-16 | | N-6=50 | | 12n+2=-36 | | 2r-3=16+21 | | -.60(y-4)=-3 | | -7x-4(-8x-16)=-14 |

Equations solver categories